(untitled) (Asian Journal of Medical and Biological Research, 2018)
An experiment was conducted in the poultry rearing unit of Sahjalal Animal Nutrition Field Laboratory, Bangladesh Agricultural University, Mymensingh for a period of 30 days by using 108 one week aged straight run Starbro broiler chicks to find out the effect of vitamin E and selenium as feed supplement for the performance of broiler. Chicks were distributed into 4 dietary treatment groups each having three replications (R1, R2, R3) and each replication contains 9 chicks. Dietary treatment groups were T0 (Control i.e. without supplemental vitamin E and Selenium), T1 (Control + 50 mg vitamin E 0.11 mg selenium per kg diet), T2 (Control + 100 mg vitamin and 0.22 mg Selenium per kg diet and T3 (Control + 150 mg vitamin E and 0.33 mg Selenium per kg diet). At end of the feeding trail the body weight of birds were 1238.28, 1231.85, 1272.59, and 1218.33 gm/bird in treatment groups T0, T1, T2 and T3 respectively which differ significantly (p<0.05) where highest body weight observed in T2 group . Body weight gain was highest in T2 (control+100mg vitamin E and 0.22 mg Selenium per kg diet) and lowest in T0 (control). Total Feed consumption during the experimental period was 2480.30, 2523.80, 2564.56 and 2555.39 g for T0, T1, T2 and T3 respectively. At 2nd and 3rd week of age, weekly feed conversion ratio were significantly (p<0.05) higher in T2 group than the other groups including control. Meat yield parameter of broilers showed significant (P<0.05) differences in dressing weight, breast weight and shank weight. Based on the above findings, the result suggest that supplementation of Vitamin E 100 mg and 0.22 mg Selenium per kg diet from ‘‘Lolyvit-ES’’ as a source of Vitamin E and Selenium may be used in broiler rations. Asian J. Med. Biol. Res. December 2017, 3(4): 521-528